Emotions and Images in Li Qingzhao’s Ci Poetry: Quantitative Analysis - Dashchenko, Hanna (Respectus Philologicus, 2019)
This article deals with ci written by the outstanding Chinese poetess of the Song dynasty Li Qingzhao (李清照, 1084–1155?) and her poetic style Yi’an ti (易安體). The empirical material for this research is the extant 60 ci of Li Qingzhao which are presented in one of the most famous collections compiled by Xu Peijun (徐培均). Having analyzed these ci I have found several correlations concerning her poetic style. Firstly, in Li Qingzhao’s poetry ci form is positively related to ci rank: the longer ci, the higher its chance of being perceived as an “outstanding” one by commentators and poets. Secondly, the way of expressing emotions is one of the main elements that make Li Qingzhao’s long ci (zhongdiao 中調 and changdiao 長調) to be perceived as the “outstanding” ones by commentators and poets and her short ci (xiaoling 小令) as nothing very distinctive. Thirdly, negatively marked emotions are dominant in Li Qingzhao’s ci, but in most cases the poetess did not mention the reason of the sorrow of the lyrical persona or the persona this emotion was connected with. Forthly, there is a strong correlation between ci form, ci rank and types of floral images in her poetry.
Keywords: Li Qingzhao; the Song dynasty; emotions; images; quantitative analysis